The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1212/wnl.0b013e3181cef84a
|View full text |Cite
|
Sign up to set email alerts
|

Mutant small heat shock protein B3 causes motor neuropathy

Abstract: The discovery of an HSPB3 mutation associated with an axonal motor neuropathy using a candidate gene approach supports the notion that the small heat shock protein gene family coordinately plays an important role in motor neuron viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 33 publications
1
56
0
2
Order By: Relevance
“…Heat shock protein 3 seems to participate in the mechanisms of cell survival (Sugiyama et al, 2000). It was shown that HSPB3 (R7S) mutation was associated with an axonal motor neuropathy (Kolb et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock protein 3 seems to participate in the mechanisms of cell survival (Sugiyama et al, 2000). It was shown that HSPB3 (R7S) mutation was associated with an axonal motor neuropathy (Kolb et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the expression of HSPB3 and MKBP/HSPB2 was induced during muscle differentiation, suggesting that the sHSP oligomer comprising HSPB3 and MKBP/HSPB2 represents an additional system closely related to muscle function (Sugiyama et al, 2000). Also it was supposed that HSPB3 plays an important role in motor neuron viability (Kolb et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the fact that mutations of several HSPB proteins (HSPB1, HSPB3, HSPB4, HSPB5, HSPB8) are associated with muscular and neurological disorders, including hereditary sensory and/or motor neuropathy (e.g. HSPB1, HSPB3, HSPB8), myofi brillar myopathy (HSPB5) and congenital cataract (HSPB4) Irobi et al 2004 ;Evgrafov et al 2004 ;Kolb et al 2010 ;Litt et al 1998 ;Vicart et al 1998 ). In this chapter we will focus on the potentially protective function exerted by HSPB8 in neurodegenerative and neuromuscular diseases and we will highlight how HSPB8 may act at the crossroad of both protein synthesis and protein degradation, thereby participating in the maintenance of proteostasis.…”
Section: Hspbs: Implication In Neurodegenerative and Neuromuscular DImentioning
confidence: 92%
“…For example, bicaudal D homolog 2 (BICD2) [187][188][189], dynactin 1 (DCTN1) [190], vesicle-trafficking protein (VAPB) [191], and cytoplasmic dynein 1 heavy chain 1 (DYNC1H1) [192,193] are identified as causative genes of some HMNs. Some are involved in cargo packaging and retrograde axonal transport [194], while mutations in some of heat shock protein family which may cause the dysregulation of protein metabolism also induce HMNs [195][196][197]. Hence, it would be interesting to investigate their roles with SMN, and whether these genes are differentially regulated, thereby leading to selective motor neurone vulnerability.…”
Section: Accepted Manuscriptmentioning
confidence: 99%